Building A Bright Future : Inclusive Education For Gen Alpha In The Digital Age - Fajriyah, Nurul; Sajawandi, Labib (International Conference on Teaching and Learning, 2025)
This study focuses on Generation Alpha who grew up in the digital era, facing challenges in education such as access gaps, lack of digital literacy, and the need for an inclusive learning approach. This article also discusses the role of technology in addressing educational inequality. Literature analysis and case studies show that technology, such as artificial intelligence (AI) and online learning platforms, can improve access and quality of education, especially for marginalized groups. However, the implementation of technology must be balanced with adequate teacher training and community involvement. This study recommends collaboration between the government, private sector, and communities in designing education policies that are responsive to the needs of Gen Alpha to achieve the sustainable development goals (SDGs) by 2030. The research method used is qualitative with library research techniques. The results show that technology strengthens access to inclusive education, although there is still a digital divide in rural areas and among low-income families. Gen Alpha is familiar with technology, but lacks critical digital literacy. Inclusive education has a positive impact on Gen Alpha engagement and learning achievement, with schools that implement inclusive principles showing better academic results. Teacher training is key to the success of digital inclusive education